Psychological Well-Being of Young Adults with Type 1 Diabetes: The Role of Social Support through Self-Management - Evi Maryam; Hera Lestari Mikarsa; Anita Zulkaida (LPPM Universitas 17 Agustus 1945 Samarinda, 2026)
Abstract:This study examines the mediating role of self-management in the relationship between perceived social support and psychological well-being among young adults with type 1 diabetes mellitus (T1DM). A total of 157 participants aged 18–40 years with T1DM completed validated measures of psychological well-being, diabetes self-management, and perceived social support. Data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM–PLS) with SmartPLS 4.1.The results show that social support has a significant direct effect on self-management (β = 0.531, p < 0.001) and psychological well-being (β = 0.249, p = 0.007), while self-management has a strong direct effect on psychological well-being (β = 0.597, p < 0.001). Furthermore, self-management partially mediates the relationship between social support and psychological well-being (β = 0.317, p < 0.001). The model demonstrates good fit (SRMR = 0.059) and moderate predictive power (R2 = 0.576). These findings indicate that psychological well-being in young adults with T1DM is influenced not only by interpersonal support but also by behavioral competence in disease management. This study contributes by integrating psychosocial and behavioral mechanisms within a mediation framework and highlighting self-management as a key pathway linking social support to psychological well-being. In the Indonesian context, where social support is often assumed to play a central role, these findings underscore that its impact on psychological well-being is largely contingent upon individuals’ capacity to translate such support into effective self-management behaviors.